Pengaruh Endhorphin Massage Terhadap Pengurangan Nyeri Punggung Pada Ibu Hamil Trimester III Di PMB Wilayah Kecamatan Pasar Rebo Jakarta Timur: Endorphin Massage, Back pain and Pregnancy TM III. - Ika natalia wulan sari (Politeknik Karya Husada, 2023)
Background: Back pain is one of the causes of discomfort in the third trimester. to reduce back pain during pregnancy, namely by non-pharmacological methods such as Endorphin Massage therapy. Objective: To determine the effect of endorphin massage on reducing back pain in third trimester pregnant women in PMB Pasar Rebo sub-district in 2023 Methods: This type of research is quantitative research, using experimental research methods with a quasi-experimental type with a One Group Pretest-Postest Design approach with controls. The population is all third trimester pregnant women (gestational age> 36 weeks) who experience back pain in BPM Pasar Rebo sub-district,Jakarta Timur DKI Jakarta. A sample of 92 TM III pregnant women were grouped into 2. Results: There is an effect of endorphin massage on back pain in pregnant women with a p value of 0.000 for third trimester mothers in PMB Pasar Rebo district in 2023. There is a very strong effect between before and after giving endorphins massage to third trimester pregnant women with a value of 0.668. Endorphin massage techniques are very effective for reducing back pain in third trimester pregnant women and can also be applied to pregnant women for relaxation while providing a sense of comfort. Keywords: Endorphin Massage, Back pain and Pregnancy TM III.